Manajemen pengetahuan dalam meningkatkan mutu dan akreditasi pendidikan Islam: Studi kasus tentang integrasi pengetahuan, kaizen, dan komunikasi pengetahuan - Zuanda, Sary; Mawar, Mawar; Hasri, Salfen; Sohiron, Sohiron (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
Islamic education has a central role in shaping individual character and morality, as well as contributing to society based on Islamic values. The management of quality management and accreditation of Islamic education is crucial in facing global challenges, with a focus on quality involving academic aspects and Islamic values. Accreditation is not only a standard of quality but also reflects the institution's commitment to continuous improvement. This article explores the key roles of quality management and accreditation, identifies challenges and details opportunities in the context of Islamic education. The research method includes a theoretical literature review, analysis of Islamic education policies, as well as a literature study of quality management guidelines. With a holistic approach, the research provides in-depth understanding to enhance the contribution of Islamic education institutions in shaping quality generations globally.